Belzutifan versus Everolimus for Advanced Renal-Cell Carcinoma - Choueiri, Toni K; Powles, Thomas; Peltola, Katriina; de Velasco, Guillermo; Burotto, Mauricio; Suarez, Cristina; Ghatalia, Pooja; Iacovelli, Roberto; Lam, Elaine T; Verzoni, Elena; Gümüş, Mahmut; Stadler, Walter M; et al. (The New England journal of medicine, 2024)
BACKGROUND: Belzutifan, a hypoxia-inducible factor 2α inhibitor, showed clinical activity in clear-cell renal-cell carcinoma in early-phase studies. METHODS: In a phase 3, multicenter, open-label, active-controlled trial, we enrolled participants with advanced clear-cell renal-cell carcinoma who had previously received immune checkpoint and antiangiogenic therapies and randomly assigned them, in a 1:1 ratio, to receive 120 mg of belzutifan or 10 mg of everolimus orally once daily until disease progression or unacceptable toxic effects occurred. The dual primary end points were progression-free survival and overall survival. The key secondary end point was the occurrence of an objective response (a confirmed complete or partial response). RESULTS: A total of 374 participants were assigned to belzutifan, and 372 to everolimus. At the first interim analysis (median follow-up, 18.4 months), the median progression-free survival was 5.6 months in both groups; at 18 months, 24.0% of the participants in the belzutifan group and 8.3% in the everolimus group were alive and free of progression (two-sided P = 0.002, which met the prespecified significance criterion). A confirmed objective response occurred in 21.9% of the participants (95% confidence interval [CI], 17.8 to 26.5) in the belzutifan group and in 3.5% (95% CI, 1.9 to 5.9) in the everolimus group (P<0.001, which met the prespecified significance criterion). At the second interim analysis (median follow-up, 25.7 months), the median overall survival was 21.4 months in the belzutifan group and 18.1 months in the everolimus group; at 18 months, 55.2% and 50.6% of the participants, respectively, were alive (hazard ratio for death, 0.88; 95% CI, 0.73 to 1.07; two-sided P = 0.20, which did not meet the prespecified significance criterion). Grade 3 or higher adverse events of any cause occurred in 61.8% of the participants in the belzutifan group (grade 5 in 3.5%) and in 62.5% in the everolimus group (grade 5 in 5.3%). Adverse events led to discontinuation of treatment in 5.9% and 14.7% of the participants, respectively. CONCLUSIONS: Belzutifan showed a significant benefit over everolimus with respect to progression-free survival and objective response in participants with advanced clear-cell renal-cell carcinoma who had previously received immune checkpoint and antiangiogenic therapies. Belzutifan was associated with no new safety signals. (Funded by Merck Sharp and Dohme, a subsidiary of Merck; LITESPARK-005 ClinicalTrials.gov number, NCT04195750.).
Keywords: senioři; Carcinoma, Renal Cell; senioři nad 80 let; indeny; lidé; doba přežití bez progrese choroby; výsledek terapie; Kaplan-Meier Estimate; Middle Aged; mužské pohlaví; aplikace orální; Kaplanův-Meierův odhad; karcinom z renálních buněk; Adult; mladý dospělý; Antineoplastic Agents; Kidney Neoplasms; transkripční faktory bHLH; Aged, 80 and over; Indenes; Young Adult; ženské pohlaví; protinádorové látky; Humans; Basic Helix-Loop-Helix Transcription Factors; Progression-Free Survival; lidé středního věku; Administration, Oral; dospělí; Female; Aged; everolimus; Everolimus; Treatment Outcome; nádory ledvin; Male